Volume 3: Design and Analysis 2011
DOI: 10.1115/pvp2011-57521
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Welded Mechanical Heterogeneity on Local Stress and Strain Ahead of Growing Crack Tips in the Piping Welds

Abstract: Primary loop recirculation (PLR) piping weld joints are more susceptible to stress corrosion cracking (SCC). But it is difficult to accurately predict SCC growth rate in PLR piping weld joints because the material and mechanical properties in weld joints are quite complicated. Especially, it is provided that hardening in the weld heat-affected zone (HAZ) might play an important role in promoting SCC growth. Considering welded mechanical heterogeneity, the local stress and plastic strain fields ahead of growing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…e yield strength of the local material in the continuous transition material model is simplified into a linear change; the "sandwich" material structure model is simplified into two materials. e yield strength mismatch coefficients of the surfacing layer and the weld material relative to the parent metal are respectively determined as M � σ sAlloy52b/σsA508 , where σ sAlloy52b and σ sA508 are the yield strengths of Alloy52 Mb and A508, respectively [23,24], and the mismatch coefficient M is shown in Table 1. Figure 9 shows the finite element model of the CT specimen.…”
Section: Materials Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…e yield strength of the local material in the continuous transition material model is simplified into a linear change; the "sandwich" material structure model is simplified into two materials. e yield strength mismatch coefficients of the surfacing layer and the weld material relative to the parent metal are respectively determined as M � σ sAlloy52b/σsA508 , where σ sAlloy52b and σ sA508 are the yield strengths of Alloy52 Mb and A508, respectively [23,24], and the mismatch coefficient M is shown in Table 1. Figure 9 shows the finite element model of the CT specimen.…”
Section: Materials Modelmentioning
confidence: 99%
“…asmedigitalcollection.asme.org/proceeding.aspx?articleid= 1627974&resultClick=3. ese prior studies (and datasets) are cited at relevant places within the text as references [23]. Advances in Materials Science and Engineering 11…”
Section: Data Availabilitymentioning
confidence: 99%
“…Several studies have demonstrated that the mechanical properties in the heat-affected zone (HAZ) of DMWJs become complex, which extremely affects the structural integrity of critical components in PWRs [11][12][13]. In addition, the material constraint effect of the DMWJ will lead to the uneven distribution of stress-strain conditions around the tip of the crack, which is one of the main factors affecting SCC [14][15][16]. In previous studies, some scholars have attempted to obtain the material mechanical properties of DMWJs by microhardness test or mini-sized tensile test [2,17,18], and the experiments in this field have shown that the strength of the weld zone and HAZ has changed dramatically.…”
Section: Introductionmentioning
confidence: 99%
“…Especially, there are continuous changes of the mechanical properties in the softening and hardening zone near the material interface, thus the interface area between two materials cannot be ignored [11]. And the stress and strain at the crack tip vary with the difference of the mechanical properties when the crack is located in different material regions [12]. However, the DMWJ was simplified to a "Sandwich" model when studying SCC behaviors in most previous studies [10,13,14].…”
Section: Introductionmentioning
confidence: 99%